AYAT AL-QUR’AN DAN HADITS TENTANG PROSES PENDIDIKAN - Susilawati Susilawati (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
Education is one of the joints in religion. The teachings of Islam have survived to this day, one of which is because there is an educational process in addition to da'wah of course. The preachers who spread to all corners of the world use the Qur'an as a guide both in terms of orientation, purpose, method or method of delivery, media and tools and even the material contained in the delivery is taken from the Qur'an. Al-Quran as the source of all sources of guidance makes it a very strong inspiration in every movement of Muslim thought. In various fields of religious Muslim society will always refer to revelation as God's word conveyed through him His prophet.